Terapia de aceptación y compromiso y duelo patológico. - Noboa Toalombo, David Andrés (2025)
Pathological grief has been recognized as a mental health problem that severely affects the well-being of bereaved individuals, generating cognitive rigidity, experiential avoidance, depressive and anxious symptoms, and denial, among others. The present study aims to characterize pathological grief and to determine the techniques and effectiveness of Acceptance and Commitment Therapy (ACT) in cases of pathological grief. This is documentary, bibliographic, descriptive-level research that follows the PRISMA methodology. Initially, 1,089 scientific articles were extracted from globally recognized databases such as Scopus, Web of Science, PubMed, SciELO, and Google Scholar, covering the period between 2015 and 2025. Boolean operators were used to search for information using terms such as “Acceptance and Commitment Therapy” and “pathological, complicated, or prolonged grief,” as well as their English equivalents: “prolonged grief,” “complicated grief,” and “acceptance and commitment.” By applying selection criteria and methodological evaluation based on the Critical Review Form–Quantitative Studies (CRF-QS) tool, the study ultimately comprised 12 scientific articles related to the study variables. The main results identified the effectiveness of the Acceptance and Commitment Therapy (ACT) approach in addressing pathological grief, employing techniques such as acceptance, values, self-as-context, present-moment awareness, cognitive defusion, and committed action—mainly using tools such as metaphors, paradoxes, and experiential exercises.